Odpowiedzi

Najlepsza Odpowiedź!
2010-01-30T13:45:04+01:00
(x+y)²-(2x-1)(2x+1)-(y-1)²-2y =
= x²+2xy+y²-(4x²+2x-2x-1)-(y²-2y+1)-2y =
= x²+2xy+y²-4x²-2x+2x+1-y²+2y-1-2y =
= -3x²+2xy

x=-√5; y=2√5.
-3x²+2xy = -3(-√5)²+2*(-√5)*2√5 = -15-20 = -35
2010-01-30T13:45:19+01:00
X²+y²-4x²-4x+1-y²+1-2y
-3x²-4x-2y+2

-3(-√5)²-4(-√5)-2(2√5)+2
-15+4√5-4√5+2= -13

2010-01-30T13:48:51+01:00
(x+y)²-(2x-1)(2x+1)-(y-1)²-2y
(x² + 2xy + y²)-(4x² + 2x -2x - 1)-(y² - 2y -1²) -2y
x² + 2xy + y²- 4x² - 2x + 2x + 1 -y² + 2y - 1 -2y
-3x² + 2xy
Teraz podstawiamy
-3(-√5)2 + 2(-√5 + 2√5)
-15 - 2√5 + 4√5
2√5 - 15

Odp: wartośc tego wyrazenia wynosi 2√5 - 15